1995
DOI: 10.1093/oxfordjournals.rpd.a082642
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Prognosis of Radiation Exposure Following the Accident at the Siberian Chemical Combine Tomsk-7

Abstract: Publication date: 1994 Document VersionPublisher's PDF, also known as Version of record Link back to DTU Orbit Citation (APA):Vakulovski, S. M., Shershakov, V. M., Borodin, R. V., Vozzhennikov, O. I., Gaziev, Y. I., Kosykh, V. S., ... Chumichev, V. B. (1994). Analysis and prognosis of radiation exposure following the accident at the Siberian chemical combine No. 750(EN) Abstract On the basis of the work (ground investigations and gamma aerial surveys) carried out jointly by the Rosgidromet organizations and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Longley and Templeton [3] report that about 60% of the beta activity released into the environment from aqueous wastes may be due to the nuclides of ruthenium. Radioisotopes of this element were also released in considerable amounts by the Chernobyl accident: their activity concentrations in the air and on the ground were similar to those of 131 I and 137 Cs [4][5][6][7][8]; the same was also found after other, although less dramatic, accidents [9,10]. Measurements of the deposition pattern of radioruthenium throughout Europe after the Chernobyl accident showed that these radionuclides were emitted in particulate form at the time of the explosion as well as in volatile form during the burning phase of the accident [11].…”
Section: Introductionmentioning
confidence: 60%
“…Longley and Templeton [3] report that about 60% of the beta activity released into the environment from aqueous wastes may be due to the nuclides of ruthenium. Radioisotopes of this element were also released in considerable amounts by the Chernobyl accident: their activity concentrations in the air and on the ground were similar to those of 131 I and 137 Cs [4][5][6][7][8]; the same was also found after other, although less dramatic, accidents [9,10]. Measurements of the deposition pattern of radioruthenium throughout Europe after the Chernobyl accident showed that these radionuclides were emitted in particulate form at the time of the explosion as well as in volatile form during the burning phase of the accident [11].…”
Section: Introductionmentioning
confidence: 60%